The impact of management transparency in promoting organizational loyalty – Field study on staff at The National Centre for Environmental compliance - Al-Ghamdi, Badr Faisal (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aims to identify the level of management transparency among the employees of the National Center for Environmental Compliance Control, and to identify the most important ways that help apply the principle of transparency in the National Center for Control, and to talk about administrative literature regarding transparency And organizational loyalty, presenting suggestions and recommendations that contribute to the embodiment of management transparency, which is reflected effectively on the organizational loyalty of employees. Statistically significant between the obstacles to applying transparency in the organization and the lack of opinion among employees working at the National Center for Control at the level of statistical significance 0. 05. The National Center for Environmental Compliance Control, who number 366 male and female employees in all departments within the Kingdom. )The study concluded that transparency affects the increase in the administrative development of the organization, and that administrative transparency works to advance the production and advancement of management in the organization, and that organizations that adopt the concept of transparency and strive for it are considered successful, and that transparency is an important tool and helps in enhancing affiliation and loyalty to the organization, and that the absence of transparency in Departments lead to the possibility of the employee exploiting the administrative powers entrusted to him or using his position, and there are administrative and financial obstacles that affect the absence of transparency, and the hierarchy of management enhances transparency. Central administration leads to the absence of transparency, and transparency works to combat administrative corruption in the organization.